A new species of Meehania (Lamiaceae) from Chongqing, China, and lectotypification of M. faberi - Bai, Zengfu; Zhou, Houlin; Zhang, Zhihua; Yi, Sirong; Chen, Xuelin; Zhang, Ji (Phytotaxa, 2025)
During a taxonomic revision of the genus Meehania (Lamiaceae), we re-evaluated the identity and nomenclatural status of Meehania faberi (Hemsley) C. Y. Wu. The protologue cited two specimens without designating a holotype; further study revealed that these specimens represent two distinct species. Therefore, in this paper, we designate a lectotype for Meehania faberi (Hemsl.) C. Y. Wu, provide a description of the new species, and assign it the name M. triangularis. The lectotypification of M. faberi and the recognition of M. triangularis clarify a long-standing nomenclatural and taxonomic confusion in the genus Meehania.